The Effectiveness of Tuba Root (Derris elliptica) and Gadung Tuber (Dioscoreahispida) to Control Bagworm Pests in Oil Palm - Santi, I.S.; Ardiani, F.; Noviana, G.; Listianto, H.; Hartono, Hartono (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine the ability of tuba root extract and gadung tuber to control bagworms in oil palm plantations. The study used a two factorial completely randomized design. The first factor is the type of insecticide, namely tuba roots and gadung tubers. The second factor is the concentration of 0%, 2.5%, 5%, 10% and 15%. Differences between treatments were tested with Duncan's multiple distances at the 5% significance level. The results showed that tuba root extract and gadung tuber extract effectively controlled bagworm pests. At a concentration of 10%, tuba root extract and gadung tuber could control these pests. This study concludes that the use of tuba and gadung root extracts can be used to control bagworms in oil palm plantations. The results of this study are expected to be useful in developing botanical insecticides to control other plant pests.